Epidemiology of Mucopolysaccharidosis Type II According to the Register of the Russian Federation - Natalia V. Buchinskaia; Ekaterina Yu. Zakharova; Yulia S. Koshevaya; Anastasia O. Vechkasova; Rostislav K. Skitchenko; Aleksandr M. Nikonov; Vera I. Kurilova; Yulia V. Maximova; Khasyanya F. Aksyanova; Elena G. Bakulina; Nina I. Kononenko; Elena V. Osipova; et al. (Turkish Archives of Pediatrics)
Objective: The study aimed to evaluate the epidemiological, clinical, and molecular data of mucopolysaccharidosis type II (MPS II) patients and their outcomes using the national registry of patients in the Russian Federation (RF).